Ultra-Wideband Analog Radio-over-Fiber Communication System Employing Pulse-Position Modulation - Sandis Migla; Kristaps Rubuls; Nikolajs Tihomorskis; Toms Salgals; Oskars Ozolins; Vjaceslavs Bobrovs; Sandis Spolitis; Arturs Aboltins (Applied Sciences)
This research presents a novel approach to 28 <semantics>GHz</semantics> impulse radio ultra-wideband (IR-UWB) transmission using pulse position modulation (PPM) over an analog radio-over-fiber (ARoF) link, investigating the impact of fiber-based fronthaul on the overall performance of the communication system. In this setup, an arbitrary waveform generator (AWG) is employed for PPM signal generation, while demodulation is performed with a commercial time-to-digital converter (TDC) based on an event timer. To enhance the reliability of transmitted reference PPM (TR-PPM) signals, the transmission system integrates Gray coding and Consultative Committee for Space Data Systems (CCSDS)-standard-compliant Reed-Solomon (RS) error correcting code (ECC). System performance was evaluated by transmitting pseudorandom binary sequences (PRBSs) and measuring the bit error ratio (BER) across a 5-m wireless link between two 20 <semantics>dBi</semantics> gain horn (Ka-band) antennas, with and without a 20 <semantics>km</semantics> single-mode optical fiber (SMF) link in transmitter side and ECC at the receiver side. The system achieved a BER of less than 8.17 × 10−7, using a time bin duration of 200 <semantics>ps</semantics> and a pulse duration of 100 <semantics>ps</semantics>, demonstrating robust performance and significant potential for space-to-ground telecommunication applications.